Public Value of "Anak Itah" Program Innovation in Palangka Raya City - Farid Zaky Yopiannor; Milka Milka (Publisia: Jurnal Ilmu Administrasi Publik, 2022)
Excellent public service is very important in the new normal life, especially in Palangka Raya City. The purpose of this study is to describe the public value of “Anak Itah” program. This program is an innovation of public service presented by the Regional Population and Civil Registry Office of Palangka Raya City. This innovation is a priority birth certificate service for people who give baby birth in hospitals that cooperate with the office. For those given priority 3-in-1 service (birth certificate, family card, and child identity card) directly at the hospital. Philosophically the word “Anak Itah” is derived from the Dayak Language which means ‘Our Children’. This study uses the public value concept as an analysis tool using qualitative methods through interviews, observation, and documentation as the data collection. The study results show that the performance implementation of “Anak Itah” program provides ease and efficiency of time to the public as users. They provide a positive response and the program is relevant to their needs in the context of public service in the post-pandemic era